Impact of an educational intervention on the knowledge of testicular self-examination and attitudes toward it - Juana Serret-Montoya; Sarait Nadja Rodríguez-Ibarra; Karla Denis Nava-Sánchez; Jessie Nallely Zurita-Cruz (Elsevier, 2023)
Introduction: There is evidence that the percentage of adolescents that practice testicular self-examination is low. Objective: To assess the short-term and long-term (6 months) impact in male adolescents of an educational intervention on the knowledge of testicular self-examination and attitude toward it. Methods: We conducted a quasi-experimental pre-test post-test study in male adolescents. A questionnaire was validated to assess knowledge on testicular self-examination and attitudes towards it (awareness, intentions, and behaviour). The educational intervention was group-based and consisted in an instructional talk with the aid of diagrams and brochures. The questionnaire was administered before and after the intervention. A follow-up was scheduled 6 months later, and the talk was delivered again, with administration of the questionnaire before and after. Results: The study included 139 adolescents with a median age of 14 years. We found an improvement in knowledge (18.3% vs 78.9%; P = 0.02) and attitude (5.6% vs 53.5%; P = 0.02) after the initial intervention. At the 6-month follow-up (n = 98), there was no change in knowledge (87.0% vs 93.0%; P = 0.671), but attitude improved after the second intervention (58.0% vs 78.0%; P = 0.009). Conclusion: An educational intervention on testicular self-examination improved the proportion of adolescents with an adequate attitude (5.6% vs 53.5%) and adequate knowledge (18.3% vs 78.9%). The repetition of the intervention at 6 months increased the proportion of adolescents with an adequate attitude (53.5% vs 86.4%). Resumen: Introducción: Se ha descrito que la autoexploración testicular se realiza en un bajo porcentaje de los adolescentes. Objetivo: Evaluar el impacto de una maniobra educativa a corto y largo plazo (6 meses) sobre el conocimiento y actitud de los adolescentes varones en la autoexploración testicular. Métodos: Se realizó un cuasi-experimento, antes y después en adolescentes varones. Se validó un cuestionario para evaluar el conocimiento y la actitud (conciencia, intenciones y comportamiento) sobre la autoexploración testicular. La maniobra educativa consistió en una charla informativa de manera grupal incluyendo esquemas y folletos. Se les aplicó el cuestionario antes y después de la maniobra educativa. Se citaron a los 6 meses posteriores y se les dio nuevamente la charla aplicándose un cuestionario antes y después de la misma. Resultados: Se incluyeron 139 adolescentes con una mediana para la edad de 14 años. El conocimiento (18.3% vs 78.9% p = 0.02) y la actitud (5.6% vs 53.5% p = 0.02) mejoró posterior a la primera charla informativa. A los 6 meses de seguimiento (n = 98) el conocimiento no se modificó (87.0% vs 93.0% p = 0.671); sin embargo, la actitud superó posterior a la segunda charla (58.0% vs 78.0% p = 0.009). Conclusión: Una maniobra educativa sobre la autoexploración testicular mejoró la proporción de una adecuada actitud (5.6% vs 53.5%) y conocimiento (18.3% vs 78.9%) en los adolescentes. El reforzamiento de la maniobra a 6 meses mejora la proporción de una adecuada actitud (53.5% vs 86.4%).